ANALISIS PENGARUH KESADARAN WAJIB PAJAK DAN PENGETAHUAN WAJIB PAJAK TERHADAP KEPATUHAN DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR (PKB) DI WILAYAH DKI JAKARTA - Mutiara Cendana; Bayu Laksma Pradana (Jurnal Bina Akuntansi, 2021)
This research was conducted with the aim of analyzing the effect of taxpayer awareness and taxpayer knowledge of taxpayer compliance in paying vehicle tax in DKI Jakarta, the independent variables in this research were taxpayer awareness and taxpayer knowledge, while the dependent variable was compliance taxpayer. This research was conducted using the Survey Research method using a questionnaire as a data collection. Sampling was done using the Simple Random Sampling method and then the data collected was analyzed by multiple linear regression. Regression test results in this research indicate that the independent variable partially has a positive effect but not significantly to the dependent variable while simultaneously the independent variable has a significant effect on the dependent variable, namely taxpayer compliance in paying vehicle tax in DKI Jakarta.